2005
DOI: 10.1016/j.jacc.2005.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Subcutaneous-Only Granulocyte-Macrophage Colony-Stimulating Factor for Collateral Growth Promotion in Patients With Coronary Artery Disease

Abstract: A subcutaneous-only, short-term protocol of GM-CSF is effective in promoting coronary collateral artery growth among patients with CAD. However, the drug's safety regarding the occurrence of acute coronary syndrome is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 11 publications
4
84
1
1
Order By: Relevance
“…Moreover, the risk of AMI was higher in coronary artery disease patients whose WBC counts increased after the administration of granulocyte colony-stimulating factor or granulocytemacrophage colony-stimulating factor administered to promote neo-revascularization. 12,13 Neutrophilic infiltration of culprit lesions in patients who died after AMI suggests that platelets and neutrophils interact at the site of ruptured plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of AMI was higher in coronary artery disease patients whose WBC counts increased after the administration of granulocyte colony-stimulating factor or granulocytemacrophage colony-stimulating factor administered to promote neo-revascularization. 12,13 Neutrophilic infiltration of culprit lesions in patients who died after AMI suggests that platelets and neutrophils interact at the site of ruptured plaques.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Animal data have similarly yielded discordant results, depending on the dose and timing of G-CSF. 12 To clarify the role of G-CSF in promoting left ventricular recovery after acute myocardial infarction, we performed an adequately powered randomized clinical trial in patients with moderate left ventricular dysfunction following anteriorwall STEMI.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, 3 other trials of G-CSF in patients with coronary artery disease were stopped early because of safety concerns: 1 trial for increased risk of in-stent restenosis 8 and 2 trials for increased risk of acute coronary syndromes. 10,11 This situation is particularly noteworthy given that research on G-CSF for patients with coronary disease or chronic left ventricular dysfunction (or both) is continuing.…”
Section: E430mentioning
confidence: 99%
“…This method may offer promise as a means of improving the efficacy of EPC transplantation for therapeutic neovascularization in the diabetic setting. However, previous data, while suggesting that G-CSF o r granulocyte-macrophage colony -stimulating factor (GM-CSF) administration did increase EPC mobilization, the therapeutic effect in patients with coronary artery disease was conflicting (174,175). More recent data have shown that transplantation of G-CSF-mobilized EPCs for the treatment of critical limb ischaemia in patients with DM is safe and effective (23).…”
Section: Epc Transplantation In Diabetesmentioning
confidence: 99%